Optimization of Tidal Transects and Traps for Mapping the Population of Mud Crabs (Scylla spp.) in Kalangan River, Tapanuli Tengah - Khobir, Muhamad Latiful; Fazri, Kurniawan; Muna, Zakyatul; Andhini, Nadia; Fuah, Ricky Winrison (Jurnal Perikanan Terpadu, 2025)
This study investigates the effectiveness of combining the low-tide transect method with the use of crab pots to map the spatial distribution of mangrove crabs (Scylla spp.) in the Kalangan River, Central Tapanuli. Mangrove crabs are ecologically and economically significant species in coastal environments, yet limited data exist on their spatial population dynamics. An exploratory survey was conducted over a period of one month across three transect sites using standardised 1×1 meter PVC frames and systematically placed crab pots. Observations included species composition, carapace size, and habitat substrate type. The findings revealed that Scylla olivacea dominated the catch (68%), with the highest density recorded at transect 2 (0.86 individuals/m2), characterised by fine, sandy-muddy substrate and moderate mangrove cover. Transect 1 showed the lowest density (0.63 individuals/m²), likely due to degraded mangrove vegetation and coarse sandy substrate. A positive correlation was observed between tidal depth and catch abundance. The results suggest that this integrated method offers a reliable baseline for assessing mangrove crab populations and can inform sustainable coastal resource management practices.